The Impact of Self-Disclosure on Academic Stress Among Final- Year College Students: A Qualitative Case Study - Khalid, Helmi Idham; Wahyuni, Sri (Guidance and Counseling Study Program, Pattimura University, 2023)
This study employed a qualitative approach in the form of a case study to examine the process of self-disclosure among students and its influence on stress levels during their thesis completion. The research focused on 10 individual students, aiming to gain a deep understanding of their experiences, thoughts, feelings, and desires. Structured and in-depth interviews were conducted, along with non-participant observation techniques. The study found that self-disclosure played a significant role in students' stress levels, with stress and depression being predominant emotions due to various factors such as academic pressure and personal issues. The Johari Window model, which emphasizes the importance of self-disclosure in interpersonal relationships, provided a theoretical foundation for understanding the responses and reactions of students. Individual counseling was also explored as a supportive process for students, allowing them to enhance self-understanding and resolve problems. The findings highlight the significance of self-disclosure in fostering healthier interactions and creating a positive academic environment. The study contributes to a deeper understanding of self-disclosure and its implications for student well-being and academic success.